Managerial accounting : concepts for planning, control, decision making - Garrison, Ray H. (Plano, Texas: Business Publications, 1985)
This book is designed for a one term course in managerial accounting, to be used by students who have already completed one or two terms of basic financial accounting. The book looks at managerial accounting through the eyes of those who must depend on accounting data in much of their work.
Includes index.
occ 17/01/2019
Loans
Keywords: Managerial accounting